KEWENANGAN KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Satria, I Wayan Yuda; Suardana, I Wayan; Darmajaya, Ida Bagus Surya (Kertha Semaya : Journal Ilmu Hukum, 2013)
Conflict between police agencies, prosecutors and the commission in handling cases ofcorruption in Indonesia. This is because the investigator is owned KPK investigatorappointed from police and prosecutors, and at a KPK investigator is still a police andprosecutors. This causes less maximum performance of KPK in eradicating corruptionlet alone deal with cases of corruption involving members of the police and prosecutors.It is hoped the Commission has the authority to appoint an independent investigatoroutside of the police and judiciary, in order to maximize the performance of the KPK ineradicating corruption in Indonesia.
Keywords: authority, commission, corruption.